Dominasi Platform Digital dan Penyalahgunaan Posisi Dominan: Telaah Ekonomi atas Putusan KPPU terhadap Google LLC dalam Skema Google Play Billing - Raden Ayu Rani Mutiara Dewi; Angelica Caesar Budianto (Visi Sosial Humaniora, 2026)
The dominance of digital platforms in the modern economy poses new challenges for the enforcement of competition law, particularly in relation to the abuse of dominant position. The practices of Google LLC, specifically through the mandatory use of Google Play Billing (GPB) in the distribution of digital applications in Indonesia, have been alleged to restrict the choices of developers and consumers and to create barriers to entry for competitors. This study employs a normative juridical method, utilizing statutory approaches, decisions of the Komisi Pengawas Persaingan Usaha (KPPU), and economic analysis of competition. The findings indicate that the GPB policy reflects an abuse of dominant position through the imposition of unilateral trading conditions and vertical integration within Google’s digital ecosystem. Decision No. 03/KPPU-I/2024 issued by the KPPU, which imposed administrative fines and mandated the opening of alternative payment methods, constitutes an important step toward restoring competitive market structures. However, the effectiveness of such corrective measures remains contingent upon continuous regulatory oversight. This study underscores the importance of incorporating economic approaches into competition law to address the dominance of global digital platforms and to safeguard the sustainability of the national creative industry.